Aetiology of rib stress fractures in rowers - Warden, S. J.; Gutschlag, F. R.; Wajswelner, H.; Crossley, K. M. (Sports Medicine, 2002)
Rib stress fractures are a common and significant problem in the rowing population. They occur in approximately 6.1 to 12% of rowers and account for the most time lost from on-water training and competition. This review discusses possible causative factors for rib stress fractures in rowers. Central to the establishment of causative factors is the identification that each rib forms part of a closed ring of bone that is completed anteriorly by the sternum and posteriorly by the thoracic vertebrae. Because of the shared sternum anteriorly each ring of bone is mechanically connected. Subsequently, during rowing individual ribs are not loaded in isolation, rather the rib cage is loaded as a complete unit. Incorporating this functioning as a complete unit a possible mechanism by which different factors contribute to rib stress fracture can be developed. In rowing, muscle factors generate loading of the rib cage. The characteristics of this loading stimulus are influenced by equipment, technique and joint factors. Rib-cage loading generates bone strain in individual ribs with the response of each rib depending upon site-specific skeletal factors. Depending on the characteristics of the bone strain in terms of the magnitude and rate of strain, microdamage may develop. The bone response to this microdamage is reparative remodelling. Whether this response is capable of repairing the damage to prevent progression to a stress fracture is dependent upon training and gender factors. Identification of these factors will generate a better understanding of the aetiology of this injury, which is required for improved prevention and treatment strategies.